THE IMPLEMENTATION OF USING ONLINE APPLICATION IN INCREASING STUDENTS’ MOTIVATION - Dhia Hasanah (International Conference on Education and Language (ICEL), 2016)
The researcher aimed to measure students’ motivation in implementing the online class learning by using application Schoology in speaking class. The participants of this research are the second semester of English Education Study Program in UBL who took speaking II class. The data that the researcher has collected is from the result of questionnaire. By using qualitative technique, the researcher can find differences between online and offline session in increasing students motivation. The questionnaire was posted after the materials have been done by the students. The questionnaire was posted in Schoology through SuperMonkey and Google forms website. The result of this research showed that the students became mor